El parto (feliz) y la Oda IV de fray Luis de León - Sánchez Jiménez, Antonio (My University, 2023)
This article studies fray Luis de León's Oda IV as a contextual poem, a genethliacon to the birth of doña Tomasa, seventh daughter of the Marquis de Alcañices. In particular, we focus on details relating to birthing and the mother and baby's health, and to how relatives reacted to these issues.